2016
DOI: 10.17159/2309-8309/2016/v15n4a1
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant bone tumours: Epidemiological data from an Orthopaedic Oncology Unit in South Africa

Abstract: Introduction: Limited data is available with regard to the epidemiology of primary malignant orthopaedic tumours in the South African clinical setting. As a result, orthopaedic surgeons have to rely on data from other countries when formulating differential diagnoses for malignant bone lesions. Existing data, however, demonstrates variance in the incidence between different geographic regions. By analysing the tumour epidemiology at our centre and comparing it to published data from other parts of the world, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In the analysis of 117 patients with primary bone tumors, Pillay et al revealed that osteosarcoma was the most common primary malignant bone tumor, accounting for 72.6% of all cases admitted to the Department of Orthopaedic Surgery, Grey's Hospital, South Africa (52). In accordance with findings reported in previous studies, the authors also confirmed the higher male to female ratio and younger age of patients, (4,28,53,54).…”
Section: Epidemiologysupporting
confidence: 68%
“…In the analysis of 117 patients with primary bone tumors, Pillay et al revealed that osteosarcoma was the most common primary malignant bone tumor, accounting for 72.6% of all cases admitted to the Department of Orthopaedic Surgery, Grey's Hospital, South Africa (52). In accordance with findings reported in previous studies, the authors also confirmed the higher male to female ratio and younger age of patients, (4,28,53,54).…”
Section: Epidemiologysupporting
confidence: 68%
“…This is in keeping with findings in the literature, which shows a higher prevalence of osteosarcoma in the second decade of life. 11 Results in this series did not reflect a bimodal distribution. Contrary to the literature, which shows a slight male predominance, this series had a slight female-to-male predominance ratio of 1.1:1.…”
Section: Discussionmentioning
confidence: 48%
“…Distal femoral tumours predominantly consist of osteosarcoma, chondrosarcoma and Ewing's sarcoma. 11,12 Neo-adjuvant chemotherapy, surgical resection with a wide margin and adjuvant chemotherapy is considered to be the mainstay of treatment of osteosarcoma and Ewing's sarcoma. 13 Reconstructive options have evolved significantly and differ for various age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ES is the second most frequent primary skeletal tumor, only after osteosarcoma, and it has the most unfavorable prognosis. It is considered very aggressive and very rare, accounting with 0.2% of all cancers and 2.9% of the entire childhood one [2,10,11]. It has an annual incidence of 3: 1.000.000, affecting mainly children, adolescents and young adults, with a peak in the second decade of life [8,9,11,12].…”
Section: Introductionmentioning
confidence: 99%